Analisis Rasio Profitabilitas dalam Menilai Kinerja Keuangan pada PT Astra Agro Lestari Tbk - Sri Wulandari; Puji Muniarty; Wulandari (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
PT Astra Agro Lestari Tbk has experienced fluctuations in profit after tax and sales over the past few years, so an analysis is needed to assess the company's level of effectiveness in generating profits. This study aims to analyze the financial performance of PT Astra Agro Lestari Tbk based on the Return on Investment (ROI) and Net Profit Margin (NPM) ratios. The study uses a quantitative approach with a descriptive method. The data used are secondary data obtained from the financial statements of PT Astra Agro Lestari Tbk for the period 2012–2024. Data analysis techniques are carried out by calculating the ROI and NPM ratios and testing using the One Sample t-Test to assess the level of the company's financial performance. The results show that the financial performance of PT Astra Agro Lestari Tbk based on the ROI ratio is in the good category, which indicates the company's ability to generate profits from its investments. However, based on the NPM ratio, the company's financial performance has not shown optimal results because the ability to generate net profit from sales is still relatively low. This finding indicates that the effectiveness of the company's investment management is better than the effectiveness of its sales management in generating net profit.